Analysis and Assessment of Conclusions in the White Book regarding Threats and Challenges in EU Common Security and Defence Policy - Wojciechowski, Sebastian (Przegląd Strategiczny, 2014)
Among the many issues that were raised in the White Book on National Security of the Republic of Poland (WBNSRP), there were also those related to the functioning of a Common Security and Defence Policy (CSDP). Its importance for the security of Poland was indicated, as well as the need on the part of EU Member States to broaden collaboration in the sphere of security and defence. The key problems occurring in the context of CSDP were also emphasised and their causes indicated. The aim of the article is to present the factors responsible for the weakening of CSDP effectiveness, ones taken into account in the White Book, and subsequently to present a Framework for their analysis in the light of further scholarship.